2020
DOI: 10.1038/s41391-020-0237-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the exosome based ExoDx Prostate(IntelliScore) EPI test in men presenting for initial Biopsy with a PSA 2–10 ng/mL

Abstract: Background The ExoDx Prostate(IntelliScore) (EPI) test is a non-invasive risk assessment tool for detection of high-grade prostate cancer (HGPC) that informs whether to proceed with prostate biopsy. We sought to assess the impact of EPI on the decision to biopsy in a real-world clinical setting. Methods We conducted a prospective, randomized, blinded, two-armed clinical utility study that enrolled 1094 patients with 72 urologists from 24 urology practices. Patients were considered for prostate biopsy at enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 19 publications
0
118
0
3
Order By: Relevance
“…men presenting for their initial biopsy with a PSA 2-10 ng/ mL where it achieved an NPV of 91%, a sensitivity of 91 and 34% specificity [16]. A recent blinded control arm utility study demonstrated that the EPI test reduced the number of biopsies when the test was negative, and helped to identify 30% more high-grade prostate cancers compared to the control arm without the EPI test result [34]. It is well established in the literature that prevalence of prostate cancer is significantly lower in a prior negative biopsy population and that this clinical feature will favorably impact test performance when included in risk assessment models (and some commercial assays) [35,36].…”
Section: Epi Performance In Predicting ≥Gg2 Pcamentioning
confidence: 99%
“…men presenting for their initial biopsy with a PSA 2-10 ng/ mL where it achieved an NPV of 91%, a sensitivity of 91 and 34% specificity [16]. A recent blinded control arm utility study demonstrated that the EPI test reduced the number of biopsies when the test was negative, and helped to identify 30% more high-grade prostate cancers compared to the control arm without the EPI test result [34]. It is well established in the literature that prevalence of prostate cancer is significantly lower in a prior negative biopsy population and that this clinical feature will favorably impact test performance when included in risk assessment models (and some commercial assays) [35,36].…”
Section: Epi Performance In Predicting ≥Gg2 Pcamentioning
confidence: 99%
“…All sites received a urine collection vessel and shipping kits; men from the rst validation study received a pediatric urine cup with instructions to only collect urine within the requested volume range, while a standardized 20 ml volume-restricted vessel was used in the second validation cohort and the utility study. Previous methods used in exosome isolation, extraction of RNA, and reverse transcriptase polymerase chain reaction (RT-PCR) were previously published (8)(9)(10)(11). The test result provides a binary low or high risk score based on a validated cut-point of 15.6 (scale 0-100) that predicts the presence of Grade group (GG) 2 or higher prostate cancer.…”
Section: Assay Methodsmentioning
confidence: 99%
“…The EPI test (Exosome Diagnostics, Waltham, MA) is a rst-catch urine exosome-based liquid biopsy assay which has been independently validated in two prospective multi-site studies and the standard of care control arm of a utility study which evaluated EPI in the biopsy decision process (8)(9)(10). Utilizing the expression levels from three genes (i.e.…”
Section: Page 4/16mentioning
confidence: 99%
“…Furthermore, as EVs contain molecules that are specific to a particular organ or disease, EV-based liquid biopsy can be optimized to be highly disease-specific. Such non-invasive tests also allow for a complementary or standalone test, providing rapid diagnosis or prognosis of diseases, such as the FDA approved EV-based biomarker for prostate cancer ExoDX (Tutrone et al, 2020).…”
Section: The Role Of Extracellular Vesicles As a Biomarker For Virus-mentioning
confidence: 99%